Patients on NOACs in the Emergency Room - Gerner, Stefan; Huttner, Hagen (Current Neurology and Neuroscience Reports, 2019)
Purpose of ReviewDespite the increasing use of NOACs, there is still uncertainty on how to treat NOAC patients presenting with neurological emergencies. Initial assessment of coagulation status is challenging but essential in these patients to provide best-possible treatment in case of ischemic or hemorrhagic stroke. Meanwhile, anticoagulation reversal strategies have been suggested; yet, the optimal management is still unestablished. The current review aims to provide up-to-date information on (i) how to identify patients with NOAC intake, (ii) which therapies are feasible in the setting of ischemic and hemorrhagic stroke as well as traumatic intracranial hemorrhage, and (iii) how to proceed with patients requiring emergency lumbar puncture.Recent FindingsDespite several expert opinions, there is still an ongoing debate which NOAC patients presenting with ischemic stroke may benefit from recanalizing strategies and whether these treatment approaches can be performed safely. Results from two phase IV trials investigating the efficacy of NOAC-specific reversal agents in case of major bleeding seem promising with regard to hemostatic parameters, but these antidotes have not been verified to clinically benefit patients, and approval by authorities in parts is still pending.SummarySpecific reversal agents are on the way and will provide new treatment options in patients with NOAC-related ischemic and hemorrhagic stroke. Up to now, the decision which patients should undergo recanalizing treatment for ischemic stroke, or which specific pharmacological reversal treatment in hemorrhagic stroke should be initiated, has to be made cautiously on an individual basis after assessing hemostatic parameters.
CRIS-Team WoS Importer:2019-06-18